Synthesis of cholera toxin B subunit glycoconjugates using site-specific orthogonal oxime and sortase ligation reactions - Dolan, Jonathan P.; Machin, Darren C.; Dedola, Simone; Field, Robert A.; Webb, Michael E.; Turnbull, W. Bruce (Frontiers in Chemistry, 2022)
The chemoenzymatic synthesis of a series of dual N- and C-terminally functionalized cholera toxin B-subunit (CTB) glycoconjugates is described. Mucin 1 peptides bearing different levels of Tn antigen glycosylation (MUC1(Tn)) were prepared via solid-phase peptide synthesis. Using sortase-mediated ligation the MUC1(Tn) epitopes were conjugated to the C-terminus of CTB in a well-defined manner allowing for high density display of the MUC1(Tn) epitopes. This work explores the challenges of using sortase-mediated ligation in combination with glycopeptides and the practical considerations to obtain high levels of conjugation. Furthermore, we describe methods to combine two orthogonal labelling methodologies, oxime and sortase-mediated ligation, to expand the biochemical toolkit and produce dual N- and C-terminally labelled conjugates.